Alkollü benzinlerin alternatif motor yakıtı olarak değerlendirilmesi - Karaosmanoğlu, Filiz (Fen Bilimleri Enstitüsü, 1990)
Günümüzde, artan nüfus ve endüstriyel gelişmelerle birlikte, e nerji gereksinimi sürekli, hızlı bir artış gösterirken; kömür, petrol, doğal gaz gibi rezervleri sınırlı fosil kaynaklı enerjiler yanında, yeni-yenilenebilir enerji kaynakları da büyük önem kazanmaktadır. Ye ni enerji kaynakları arasında biokütle en büyük potansiyele sahiptir. Biokütle kaynaklarının enerji amaçlı en önemli değerlendirilme alanla rından biri alkollerin alternatif motor yakıtı olarak kullanımıdır. Bu çalışmada da, günümüz benzin motorlarında tasarım değişikliği ge rektirmeyecek şekilde, benzine katılabilecek maksimum alkol miktarı olarak önerilen %2Ö (hacimsel) oram gözönüne alınarak, hazırlanan me tanollü ve etanol lü benzinlerin alternatif motor yakıtı olarak değer lendirilebilirlıği incelenmiştir. Deneysel çalışmaların, ilk bölümün de, isopropanol., n-propanol, isobutanol, n-butanol, isoamilalkol, n-amilalkol ve füze! yağı kullanılarak, alkol-benzin karışımlarında faz ayrışma sorunu çözümlenmiş, karışımların faz ayrışma olayı geniş olarak incelenmiştir. î kinci bölümde ise füze! yağı katkılı alkollü benzinlerin ASÎM yöntemlerine göre yakıt özellikleri belirlenerek, el de edilen sonuçların benzin özellikleri ile uyum gösterdiği saptanmış tır. Çalışmanın son bölümünde ise Renault 12 test motorunda yapılan çalışmalar ile alkollü benzinlerin motor karakteristikleri ve egzoz gazı emisyonları belirlenmiştir.

Energy is one of the most important milestones of human life. Supply-demond irregularities, consecutive oil crisis followed by fluctuations and rise in oil prices led countries to search for new energy sources. As a result, besides the conventional fossil fuels like coal, petroleum, natural gas evaluation of alternative energy sources like the sun, wind, geothermal, hydro! ic, hydrogen and bio- mass were taken into consideration in order to meet the increasing energy demand. Biomass sources have an important place in new and renewable energy sources. World potential of the new and renewable energy sources are given in Table 1 as TOE (tons oil equivalent). Although the new energy sources are used in a limited manner today, these sources seem to gain importance within the world's energy supply in future. One of the ways of evaluating the biomass sources in the field of energy is converting them to alcohols by biotechnological methods which than can be used as engine fuel. Gasolines that contain alcohol up to 20 vol % can safely be used in today's Otto engines without any need for a design change. Table 1- World Production Potential of the New and Renewable Energy Sources, Million TOE/Year ¦ The positive results due to the evaluation of alcohol -gasoline blends as engine fuel alternatives can be summarized as follows: Alcohol -gasoline blends are the first step proposed in the evaluation of new and renewable energy sources in Otto engines, so using them as engine fuels will mean an improvement in the introduction of the new energy sources and evaluation possibilities of biomass potential will thus increase. Addition of alcohol to gasoline will decrease the overall gasoline consumption. This is an important point for Turkey as 90% of the oil consumed in the country is provided through imports. According to the 1988 figures gasoline makes up 2 174 082 tons of the civil petroleum products consumption which is 20 147 354 tons. It can easily be observed that the gasoline consumption is foreign dependant and the import expenses are quite a heavy burden to the country 's vi economy. Besides a reduced gasoline consumption is important for the petrochemical industry whose raw material is dependant on crude petroleum. Due to the addition of alcohols which have high octane numbers to gasoline and their continious use as alternative engine fuel will cease the environmental pollution caused by lead and even tually positive decrease will also be observed in the other exhaust emissions. In adapting the alcohol-gasoline blends into everyday use in Turkey benefits for the country's economy must be evaluated while scientific research strengthening the idea must also be put forward. Alcohol -gasoline blends are in fact a three component system of gasoline-alcohol and water due to the hygroscopic character of the alcohols. The most important problem in using such blends as engine fuel is their seperation possibility into two liquid phases due to several factors. When such a two phased system is tried to be used in an engine several serious problems occur. Therefore, in the evaluation of alcohol -gasoline blends as engine fuel the first step should be solving the phase seperation problem hence obtaining a homogenous mixture. Therefore in this work the phase seperation problem in gasolines blended with methanol or ethanol was solved by adding special additiv es to the blends and due to the positive results obtained from the fuel property and engine tests the stable blend fuels were proposed as a fuel alternative for today's Otto Engines. Mixtures used in the research were prepared by adding Merck grade pure methanol and distilled (b.p. 78.15DC) ethanol containing 4.4 weight % water to the four unleaded gasoline samples of different composition provided from TÖPRAŞ tzmit Refinery. The alcohol ratio in the mixtures is 5, 10, 15, and 20 % by volume. Research work was realized in three steps: 1. Solving the phase seperation problem of the alcohol-gasoline blends. 2. Determining the fuel properties of alcohol -gasoline blends 3. Engine tests, engine characteristics and exhaust emmission values of alcohol-gasoline blends. The phase seperation problem of gasoline-alcohol, blends is solved by using isopropanol, n-propanol, isobutanol, n-butanol, isoamyl- alcohol, n-amylalcohol and fusel oil fraction as additives. The fraction of molasses fusel oil which contains 0.1 vol % water and which boils above 120°C was used in the experiments. According to the results of the GLC analysis fermentation amyl alcohol s make up 86.5 % by weight of this fraction. vii According to the results obtained, the additives mentioned can effectively solve the phase seperation problem and they all have approximately the same effect on the phase seperation temperature of the alcohol-gasoline blends. The chemical composition of the gasoline used, environmental temperature, alcohol content and water tolerance of the blend, using ethanol or methanol as the alcohol component all are factors that influence the phase seperation in alcohol-gasoline blends. Fusel oil which is one of the additives used in the experiments is a by-product of ethanol production. Using fusel oil and its already defined fraction as an additive is a new way of evaluating the by product and it is proposed for the first time in this research work. The essential results concerning the change in phase seperation tem peratures of fusel oil added alcohol -gasoline blends are as follows: 1. An increase in the amount of the fusel oil fraction within the alcohol -gasoline blends of known alcohol and water content increases the water tolerance values and decreases the phase seperation tempera tures. 2. The chemical composition of the gasoline used is very important for the alcohol-gasoline blends. An increase in the aromatic charac ter of the gasoline increases the phase seperation temperatures of the blends. 3. In a gasoline-alcohol-water and fusel oil fraction system environmental temperature is vitally important for the stability of the blend. An increase in temperature means an increase in the water tolerance of the blend while the amount of additive needed for a stable blend decreases. 4. Using ethanol or methanol in alcohol gasoline blends causes some differences in the phase seperation temperatures. This fact is due to their solubility differences in the hydrocarbons; for instance solu bility of ethanol is independant of the type of the hydrocarbon. There fore, same phase seperation temperatures were observed for alcohol -gaso line blends prepared with gasolines rich in aromatics and saturates. On the contrary, solubility of methanol in aromatic hydrocarbons is higher compared to other hydrocarbons; therefore, in methanol -gasoline blends prepared with gasoline rich in saturates different phase sepe ration temperature change is observed than the ethanol-gasoline blends. Ethanol --gasoline blends are more water tolerable than methanol- gasoline blends. Therefore, ethanol-gasoline blends prepared with the same gasoline and containing same amounts of water, alcohol and fusel oil fraction had lower phase seperation temperatures than methanol - gasoline blends. In the second part of the research ASTM fuel properties of the viii fuel oil fraction added stable blends were compared with those proper ties of their component gasolines and a general accordance between the results was observed. The fuel property tests and their ASTM numbers are as follows: 1- Density (ASTM D 1298) 2- Distillation Test (ASTM D 86) 3- Reid vapor pressure Test (ASTM D 323) 4- Octane number Research method (ASTM D 2699) Motor method (ASTM D 2700) 5- Corrosion Test This test was applied in two different ways: a) Copper corrosion test (ASTM D 130) b) Test proposed for gasohol (gasoline containing 10 vol % pure ethanol) by The American Society for Testing and Materials. This test was both applied to alcohol-gasoline blends and to the same blends containing 10 vol % water. The materials test ed according to ASTM D 665 were aluminium, zinc, magnesium, lead, zinc coated steel and PVC. Engine tests were realized in a Renault 12 (1200 cc.) laboratory test engine at 21°C, 80% humidity, 101.3 kPa. CO and hydrocarbon emissions were continiously measured with a Hamilton Analyzer throug- out the test period. Nitrogen oxides were determined accordinq to VDI 2456 method. Important results obtained from the engine and ex haust emission, tests using the blend fuels, component gasolines and commercial gasoline can be summarized as follows: 1. Results of the engine tests and engine characteristic values determined through these tests using alcohol blends and plain gaso line all are in accordance within themselves. In alcohol-gasoline blends an increase in specific fuel consumption and thermal effici ency was observed when compared with gasoline itself while power and moment values decreased. It must be noted that these tests could only be carried out under some predetermined conditions. £ngi ne characteristic values under different conditions such as different spark advances, compression ratios and throttle opening positions must be determined and engine performance maps for alcohol -gasoline blends must be constituted. 2. Using alcohol-gasoline blends as engine fuel has positive effects from the exhaust emissions' point of view. In the experi ments carried out at 1/3 and 2/3 throttle opening positions a rapid decrease in CO emission values was observed while nitrogen oxides emitted were approximately at the same level with those in the case of gasoline. On the other hand, in the 1/3 position hydrocarbon emissions were higher compared to gasoline while in the 2/2 position they were approximately the same or lower than the values obtained for gasoline. With a more detailed investigation on engine charact eristics as mentioned above i% will also be possible to comment on the general tendancy of the exhaust emissions. The blends used in the experiments were all prepared with unleaded gasoline, therefore ix the deformation of the seat material during long term engine tests using b3end fuels must be thoroughly investigated and the most con venient seat material must be selected accordingly.
Evaluation of alcohol-gasoline blends as engine fuel alternative
Tez (Doktora)--İTÜ Fen Bil. Enst., 1990
Keywords: Alternatif yakıtlar; Benzin-alkol karışımı; Benzinli motorlar; Motor yakıtları; Alternative fuels; Gasoline-alcohol mixture; Gasoline engines; Motor fuels